2011
DOI: 10.1111/j.1365-2591.2011.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cusp coverage on the fracture resistance of premolars with endodontic access cavities

Abstract: Cusp reduction and coverage with composite resin significantly increased the fracture resistance of premolar teeth with MOD and endodontic access cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 30 publications
(63 reference statements)
6
38
1
Order By: Relevance
“…Fracture resistance of teeth is known to decrease after endodontic treatment, and the amount of stress in dental tissues increases in the face of functional forces. Many studies have revealed the ideal restorative approaches that increase fracture resistance of remaining dental tissues after endodontic treatment and enable minimal stress transmission [10, 18, 19, 2527]. The use of woven fiber, fiber posts, and cusp capping was generally preferred in these studies to strengthen tooth structure.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture resistance of teeth is known to decrease after endodontic treatment, and the amount of stress in dental tissues increases in the face of functional forces. Many studies have revealed the ideal restorative approaches that increase fracture resistance of remaining dental tissues after endodontic treatment and enable minimal stress transmission [10, 18, 19, 2527]. The use of woven fiber, fiber posts, and cusp capping was generally preferred in these studies to strengthen tooth structure.…”
Section: Discussionmentioning
confidence: 99%
“…Direct restorations with resin composite have been investigated in both experimental and clinical studies, with favourable reports. [6][7][8][9][10] However an inherent problem with resin composites is polymerization shrinkage and associated stresses in tooth structure and at the tooth-restoration interface, with subsequent problems of marginal leakage, recurrent caries and possible tooth fracture, (summarized in [11][12][13]. The use of low shrink composites, flowable liners and bases has been suggested to overcome this problem, [14][15][16][17] considering the increased placement of resin composite in posterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several attempts have been made to improve the fracture resistance of endodontically treated teeth with different post systems, and could change the rate of root fracture 4,8) . Other studies recommend cusp coverage to restore the fracture resistance 9) , because they protect cusps which are not shifted to the outside 21) . Direct use of composite resins to restore root-filled premolars is deemed to be possible 13,22) .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies revealed that endodontically treated maxillary premolars without fiber posts exhibited similar fracture resistance to those with a post 5,8) . Several authors recommend cusp coverage to restore weak posterior teeth 9) . Actually, some clinical trials achieved promising results with this method for the restoration of severally destroyed posterior teeth 10,11) .…”
Section: Introductionmentioning
confidence: 99%